Pelletization and quality evaluation of torrefied selected biomass with microwave absorber - Obiora S. Agu; Lope G. Tabil; Edmund Mupondwa; Bagher Emadi; Duncan Cree (Results in Engineering)
Camelina straw and switchgrass are herbaceous biomass feedstock for biofuel production, and they can be produced in large quantities in North America. The current study investigated the pelleting of optimized microwave torrefied camelina straw and switchgrass with and without biochar and high-density polyethylene (HDPE) as a binder during densification. The primary research focused on the influence of the binder levels (0, 10, and 25 wt.%) added to the torrefied biomass on pellet quality. The addition of 25 wt.% HDPE significantly improved pellet characteristics, such as pellet density, dimensional stability, tensile strength, durability, and the effects of interparticle interaction on pellet properties. The pelleting conditions were optimized and validated using the torrefaction treatment conditions: microwave power 520 W, biochar 20 wt.%, residence time of 20 min, and binder level of 25 wt.% HDPE. The X-ray photoelectron spectroscopy (XPS) analysis of the pellet ash revealed that adding HDPE increased the carbon and decreased the oxygen contents. Thus, the oxygen/carbon ratio had similarities to ash from the XPS and elemental analysis results and exhibited uniform chemical properties between the ash surface and torrefied yield fraction ash. The torrefied camelina straw and switchgrass with and without biochar/HDPE pellet ash characteristics indicated a strong potential for using these herbaceous biomass for heat production and electricity generation.